Key developments and hotspots of exosomes in Alzheimer’s disease: a bibliometric study spanning 2003 to 2023 - Liu, Siyu; Geng, Daoying (Frontiers in Aging Neuroscience, 2024)
Background Alzheimer’s disease (AD) is a degenerative illness of the central nervous system that is irreversible and is characterized by gradual behavioral impairment and cognitive dysfunction. Researches on exosomes in AD have gradually gained the attention of scholars in recent years. However, the literatures in this research area do not yet have a comprehensive visualization analysis. The aim of this work is to use bibliometrics to identify the knowledge constructs and investigate the research frontiers and hotspots related to exosomes in AD. Methods From January 2003 until June 2023, we searched the Web of Science Core Collection for literature on exosomes in AD. We found 585 papers total. The bibliometric study was completed using VOSviewer, the R package “bibliometrix,” and CiteSpace. The analysis covered nations, institutions, authors, journals, and keywords. Results Following 2019, the articles on exosomes in AD increased significantly year by year. The vast majority of publications came from China and the US. The University of California System, the National Institutes of Health, and the NIH National Institute on Aging in the US were the primary research institutions. Goetzl Edward J. was frequently co-cited, while Kapogiannis Dimitrios was the most prolific author in this discipline with the greatest number of articles. Lee Mijung et al. have been prominent in the last two years in exosomes in AD. The Journal of Alzheimer’s Disease was the most widely read publication, and Alzheimers & Dementia had the highest impact factor. The Journal of Biological Chemistry, Proceedings of the National Academy of Sciences of the United States of America, and Journal of Alzheimer’s Disease were the three journals with more than 1,000 citations. The primary emphasis of this field was Alzheimer’s disease, exosomes, and extracellular vesicles; since 2017, the number of phrases pertaining to the role of exosomes in AD pathogenesis has increased annually. “Identification of preclinical Alzheimer’s disease by a profile of pathogenic proteins in neurally derived blood exosomes: a case–control study” was the reference with the greatest citing power, indicating the future steered direction in this field. Conclusion Using bibliometrics, we have compiled the research progress and tendencies on exosomes in Alzheimer’s disease for the first time. This helps determine the objectives and paths for future study.